A Case report of Wolfram Syndrome - Samaneh Norooziasl; Seyed Alireza Javadinia (مجله دانشگاه علوم پزشکی بیرجند, 2013)
Wolfram Syndrome is a neurodegenerative autosomal recessive disorder. The occurrence of the disease should be suspected if non-autoimmune insulin-dependent diabetes occurs in an under-sixteen year old person having bilateral optic nerve atrophy. Diabetes insipidus (DI), neurosensory deafness, urinary track disorders, and nervous system complications are also seen in this disorder. The current report presents a 13-year-old female patient with diabetes mellitus type I (since age 4) along with recurrent urinary infection and enuresis and progressive renal failure (since age 10). Bilateral optic atrophy was evident on fondues examination. The patient also had diabetes insipidus, neurosensory deafness, neurogenic bladder, short stature, combined with delayed sexual maturity.